2018
DOI: 10.1038/s41598-018-33297-y
|View full text |Cite
|
Sign up to set email alerts
|

A dimeric fluorescent protein yields a bright, red-shifted GEVI capable of population signals in brain slice

Abstract: A bright, red-shifted Genetically Encoded Voltage Indicator (GEVI) was developed using a modified version of the fluorescent protein, tdTomato. Dimerization of the fluorescent domain for ArcLight-type GEVIs has been shown to affect the signal size of the voltage-dependent optical signal. For red-shifted GEVI development, tdTomato was split fusing a single dTomato chromophore to the voltage sensing domain. Optimization of the amino acid length and charge composition of the linker region between the voltage sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 32 publications
1
30
0
Order By: Relevance
“…However, the resulting GEVI Ilom shows similar performance as GEVIs based on tandem dimer tdTomato described here. In addition, similar to our results introduction of charged outward oriented residues on the FP surface failed to increase the dynamic range of Ilom sensitivity 45 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, the resulting GEVI Ilom shows similar performance as GEVIs based on tandem dimer tdTomato described here. In addition, similar to our results introduction of charged outward oriented residues on the FP surface failed to increase the dynamic range of Ilom sensitivity 45 .…”
Section: Discussionsupporting
confidence: 91%
“…Unlike with the GFP-based GEVIs, we showed that combinatorial effect of mutations of these residues lowers the voltage sensitivity compared to GEVI based on native FPs. In a recent study, the potential of dimerization of the FP for GEVI development was explored using red-shifted dimer FP dTomato 45 . However, the resulting GEVI Ilom shows similar performance as GEVIs based on tandem dimer tdTomato described here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tracking membrane potential of cells, especially neurons, using fluorescence methods is of high interest and is an active field of research (change of membrane voltage causes change of fluorescence efficiency) [1][2][3][4][5][6][7][8][9][10]. To determine membrane voltage, a variety of voltage sensitive dyes [11][12][13], genetically encoded calcium indicators (GECI) [4,14,15], and genetically encoded voltage indicators (GEVI) based on voltage sensing domains (VSD, composed of four trans-membrane helices and fused fluorescent proteins) [16][17][18][19][20] and on microbial rhodopsins (composed of seven trans-membrane α-helices with covalently bound retinal, using the intrinsic fluorescence of retinal [9,10,[21][22][23] or the modified fluorescence from attached fluorescent proteins [19,23,24] or dyes [12]) are in use. Often, Förster-type resonance energy transfer (FRET) is involved in dye or fluorescent protein connection to VSDs and rhodopins [12,25].…”
Section: Introductionmentioning
confidence: 99%
“…Though the construct showed some weak signals (see SI) it did not show a large change in the light emission as observed in the FRP-VSD-eluxAB-YPet. Dimerization of the acceptor fluorescent protein causes voltage dependent FRET in fluorescent GEVIs [67]. We ruled this mechanism using a dark mutant of YPet that showed voltage dependent bioluminescent signal but no acceptor resonance energy transfer.…”
Section: Discussionmentioning
confidence: 99%